The Comparison of Service Quality Between Alfamart and Indomaret Minimarket in Kupang City - Tloim, Asniyati; Benu, Yessi (CV. Jala Berkat Abadi, 2023)
The research is entitled “The Difference of Service Quality Between Alfamart minimarket and Indomaret Minimarket in Kupang City”. The problem formulation in this research was whether there was difference of service quality reviewed from physical evidence(tangible), empathy, reliability, responsiveness, assurances between Alfamart and Indomaret minimarket in Kupang city. The aim of this research was to analyze the difference of Service Quality Between Alfamart minimarket and Indomaret Minimarket in Kupang city reviewed from service qualities aspect that were physical product, empaty, reliability, responsiveness, and assurance. The sampling method used was non-probability sampling technique. The primary data collection method is with questionnaires. The primary data used in this research amounted to 96 people per object then the total samples were 192 people. The analysis tool used was an independent sample t- test. The research result showed that there was no difference between service quality of Alfamart and Indomaret Minimarket in Kupang city reviewed from five variables that were tangible, empathy, reliability, responsiveness, assurances.